PENGARUH ARTIFICIAL INTELEGEN DAN TECHNOLOGY ACCEPTED MODEL TERHADAP KEPUTUSAN MEMBELI GENERASI MELLENIAL DI KODYA JAKARTA TIMUR - Tatag Herbayu (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2022)
This study aims to determine the effect of artificial intelligence and technology acceptance model on the decision to buy products by millennial generation. Researchers used descriptive quantitative research methods in this study. The results obtained based on a questionnaire distributed online. Artificial intelligence and technology acceptance model,respectively a positive and significant effect, on the decision to buy products by the current millennial generation. While both artificial intelligence and technology acceptance model also influence together based on the results of data processing. So it can be concluded that artificial intelligence and technology acceptance model each have a positive and significant influence on the decision making process to buy products made by millennial generation.